Clinico-demographic Profile and coinfections among hospitalized children with chikungunya in a tertiary care hospital of North India: lessons learnt - Deswal, Shivani; Yadav, Ajeet Kumar; Dey, Soumya; Yadav, Tribhuvan Pal; Yadav, Chander Prakash (Indian Journal of Child Health, 2018)
Background: Chikungunya is a vector-borne arboviral disease. Children are known to have atypical manifestations. Overlapping features with other infections can make the diagnosis difficult. Objective: The objective was to study the clinicodemographic and laboratory profile of chikungunya and the impact of coinfections on the course and outcome among hospitalized children. We conducted the study during a large outbreak of chikungunya in the national capital. Materials and Methods: A retrospective analytical study was conducted on children admitted from July to November 2016 at a tertiary care hospital in North India. Case records of all hospitalized children (1 month–14 years) with immunoglobulin M positive chikungunya serology were reviewed. Children were categorized into Group A (isolated chikungunya infection) or Group B (coinfection) after entering baseline data, clinical, laboratory, and management details in a pre-designed case record pro forma. Groups A and B were compared to see any statistically significant difference in the clinical and laboratory parameters using appropriate statistical tests. Results: Of 102 children, 45 (44.1%) had isolated chikungunya and 57 (55.9%) had chikungunya with other coinfections. In the coinfection group, 37 (36.3%) had dengue, 7 (6.8%) enteric, 6 (5.9%) malaria, 5 (4.9%) pyomeningitis, and 2 (2%) viral hepatitis-A. Vomiting and splenomegaly (p